Graphmatica Software – Theory and practice in the incorporation of TDIC as a pedagogical tool (Research, Society and Development, 2020)
This report aims to present a review of chapter 18 of the book "Learning Objects: Theory and Practice", titled DIGITAL TECHNOLOGIES IN The CLASSROOM: the USE OF GRAPHMATICA SOFTWARE AS a PEDAGOGICAL TOOL. The theme emerges about the importance of evaluating the construction of student knowledge through the use of Graphmatica Software in the study of analytical geometry, elaborating activities to visualize the graphs to be applied in the 3rd year of high School. The research had a qualitative, quantitative and bibliographic methodological approach, and a study from data collection through a questionnaire. Among the contributions arising from the process, the software approach was highlighted in the classroom context in the teaching of mathematics. Based on the results, the importance of using digital technologies is emphasized.